Identification and characterisation of microsatellite DNA markers in order to recognise the WSSV susceptible populations of marine giant black tiger shrimp, Penaeus monodon - Chakrabarty, Usri (Vet Res, 2015)
White spot disease (WSD) which is caused by white spot syndrome virus (WSSV) creates severe epizootics in captured and cultured black tiger shrimp, resulting a huge loss in the economic output of the aquaculture industry worldwide. Performing selective breeding using DNA markers would prove to be a potential cost effective strategy for long term disease control in shrimps. In the present investigation, microsatellite DNA fingerprints were compared between naturally occurring WSSV resistant and susceptible populations of Penaeus monodon. After PCR with a set of shrimp specific primers three reproducible DNA fragments of varying sizes were found, among which 442 bp and 236 bp fragments were present in considerably higher frequencies in the WSSV susceptible shrimp population (p ≤ 0.0001). After WSSV challenge experiment the copy no. of WSSV was determined using real-time PCR, where it was found to be almost 4 × 10(3) fold higher in WSSV susceptible shrimps than in the resistant ones. Thus, these microsatellite DNA markers will be useful to distinguish between WSSV susceptible and resistant brood stocks of P. monodon. Sequencing studies revealed that these DNA markers were novel in P. monodon. Highest WSSV resistance using these DNA markers, was observed in the shrimp populations of Andaman Island and Chennai among the different coastal areas of India, suggesting these places as safe for specific pathogen resistant brood stock shrimp collection. This study will be a very effective platform towards understanding the molecular pathogenesis of WSD for generation of disease free shrimp aquaculture industry.